Understanding Romance Scammers Through the Lens of Their Victims: Qualitative Modeling of Risk and Protective Factors in the Online Context - Wang, Fangzhou (American journal of criminal justice, 2024)
Romance scams represent a form of online crime with origins in the physical world, including FTF and physical mail scams. Although these crimes have been revolutionized by the affordances inherent in the technological advantages of social media and the internet, less is known about the foreground characteristics of the offense, including the preferred targeting and scamming strategies of romance fraudsters as facets of a larger process of communication and deception between offenders and victims. Much of the research has focused on the existence and mechanics of such fraud schemes and less on how reciprocal communication between offenders and victims, governed by measurable principles of impression management and deception can underpin the overt manipulation of victims into parting with their financial resources. Our goal in the current research is to identify risk and protective factors for those targeted by romance scam offenders to develop a model for victim vulnerability and resilience. Using data developed through a systematic collection of victim recounts of their scamming experiences from online sources (Nfemale = 32 and Nmale = 20), our findings point to a reciprocal model between victims and offenders through identifying four main themes in victims’ descriptions of their scamming experiences. Such an effort allows us to delineate important risk signals we identify as crucial for future research and prevention efforts. The findings of this study speak to the importance of understanding social and behavioral interactions between victims and offenders during a romance scam as critical to establishing risk and protective factors of victims, which further inform preemptive prevention efforts.